Photocatalytic degradation kinetics of Reactive Black 5 (RB5) dyestuff on TiO2 modified by pretreatment with ultrasound energy - Saygi, Berrin; Tekin, Derya (SPRINGER, 2013)
In the photocatalytic degradation of Reactive Black 5 (RB5) dyestuff, the photocatalytic activity of Riedel-de Haen brand TiO2, whose photocatalytic activity is low, was increased by ultrasound energy applied as a photocatalyst in the experiments. The BET surface areas of TiO2 with and without ultrasound treatment were 38 and 4 m(2)/g. The initial dye concentration, temperature and the effects of light intensity on the photocatalytic degradation kinetics of RB5 were examined. It was determined that the photocatalytic degradation follows pseudo-first order kinetics, depending on the dye concentration. The activation energy of the reaction was determined to be 29.3 kJ/mol.
Keywords: Photocatalysis; Ultrasound; Modified TiO2; Degradation kinetics; Reactive Black 5 Dye; AZO-DYES; SONOPHOTOCATALYTIC DEGRADATION; METHYL-ORANGE; OXIDATION; FENTON; WATER; Chemistry